An achievement test for Chinese preschool children: Validity and social correlates. (October 2020) - Yeung, Wei-Jun Jean; Chen, Xuejiao; Ding, Xiao Pan; Cheung, Mike W.-L.
Early childhood is a crucial period for human development that has long-term implications for one's life trajectories. During the years before formal schooling, brain size and structures, as well as cognitive abilities, undergo rapid development. Children's cognitive abilities develop by leaps and bounds and show great malleability. Cognitive development during early childhood exerts a long-lasting influence on children's life chances in adulthood. In China, however, there is no established reliable early childhood achievement test that can be used in a study. This study validates an achievement test for Chinese preschoolers. We analyze data from a nationally representative sample of children aged three to six who participated in the Zhang-Yeung Test of Achievement for Chinese Children (ZY-TACC) in 2012. The instrument consists of a 28-item verbal test and a 24-item numeracy test. Our evaluations indicate a satisfactory level of difficulty, as well as high internal consistency and reliability. This instrument exhibits ample ability to distinguish among children of different ages and varying family backgrounds in ways consistent with previous literature. Children's test scores are also found to correlate in the expected direction with their behavioral indicators. We demonstrate that the ZY-TACC is a psychometrically robust, culturally and contextually appropriate instrument for assessing Chinese preschool children's achievement. The instrument can make a significant contribution to research on early childhood development in China.